THE BUSINESS PERIODICALS OF GERMANY. - Schmaltz, Kurt (The Accounting Review, 1930)
Abstract This article focuses on the comparative analysis of the business periodicals of Germany and the U.S. Periodicals like "The Accounting Review" and "The Journal of Accountancy" simply do not exist in Germany, at least not as scientific periodicals. The German periodicals cover the whole field of business economics. Only recently is specialization noticeable, based upon purely practice considerations, and this, to be sure, partly under the influence of its American models. The German periodicals can best be compared with the Harvard Business Review, although even there the field of finance and marketing is prominently emphasized. Some of the articles therein, would also, in Germany, be considered in the field of political economy. One might object that the contrast between the working out of the study of business economics in the United States and in Germany is not quite so sharp as seems emphasized here. In Germany the two subjects, Political Economy and Business Economics, are two widely separated sciences. This may occasionally be deplored, yet each of the subjects places value upon its particular point of view, although both are working' toward the same objective.